The Website Optimization and Analysis on XYZ Website using the Web Core Vital Method - Kristian Handoko Wijaya Sukardjoh; Zahra, Amalia (AI Society & STMIK Indonesia, 2023)
XYZ website is a business website that operates in the field of e-commerce which is implemented through websites and applications, for several years the website has had a percentage of users' usage speed which has decreased quite a bit and has become old, due to lack of maintenance of some of the features contained in the website application which have an impact on the lack of customer interest in buying goods on the XYZ website and more influential in terms of access from searching e-commerce notifications from Google that if the percentage of websites decreases over a long period of time, this will result in websites not being allowed to publish advertisements. In this study, we analyze the problem to understand the problem starting from small things, namely from the use of programming languages, the data provided, the use of writing code, third party or vendor support, filling out website content, and websites using vital core web architecture. So that the website used has good comfort, accelerates the use of the website which can be affected by the large number of customer visitors, and can facilitate the development team's performance in management and maintenance and provide many positive things from customers so that business runs fast and provides convenience for customers and the XYZ website can received by Google.